2018
DOI: 10.7717/peerj.4966
|View full text |Cite
|
Sign up to set email alerts
|

Multi-omic profiling to assess the effect of iron starvation inStreptococcus pneumoniaeTIGR4

Abstract: We applied multi-omics approaches (transcriptomics, proteomics and metabolomics) to study the effect of iron starvation on the Gram-positive human pathogen Streptococcus pneumoniae to elucidate global changes in the bacterium in a condition similar to what can be found in the host during an infectious episode. We treated the reference strain TIGR4 with the iron chelator deferoxamine mesylate. DNA microarrays revealed changes in the expression of operons involved in multiple biological processes, with a prevale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Together with iron, riboflavin-derived molecules are the most important redox cofactors in enzymatic reactions [ 67 ]. Probably owing to this common property, iron and riboflavin metabolism has been reported to be highly related in some bacteria [ 37 , 38 , 68 , 69 , 70 , 71 , 72 ]. In V. cholerae , we have documented that riboflavin and iron reciprocally regulate their provision systems [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Together with iron, riboflavin-derived molecules are the most important redox cofactors in enzymatic reactions [ 67 ]. Probably owing to this common property, iron and riboflavin metabolism has been reported to be highly related in some bacteria [ 37 , 38 , 68 , 69 , 70 , 71 , 72 ]. In V. cholerae , we have documented that riboflavin and iron reciprocally regulate their provision systems [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…When compared with the findings of a genome and transcriptome study, proteomics and metabolomics appears to be closer to the phenotype, so it is more suitable for mechanistic studies, disease typing, and biomarker discovery (Jimenez-Munguia et al, 2018;Li & Shui, 2019;Wilmanski et al, 2019). Previous human studies have identified a few candidate metabolites for BMD alteration (Miyamoto et al, 2018;You et al, 2014), while more research about proteome studies is needed to better understand the molecular changes associated with low BMD in OP and ON, especially in postmenopausal women who are more susceptible to experiencing fragility fractures.…”
Section: Introductionmentioning
confidence: 99%
“…When compared with the findings of a genome and transcriptome study, proteomics and metabolomics appears to be closer to the phenotype, so it is more suitable for mechanistic studies, disease typing, and biomarker discovery (Jimenez-Munguia et al, 2018;Li & Shui 2019;Wilmanski et al, 2019). Previous human studies have identified a few candidate metabolites for BMD alteration (Miyamoto et al, 2018;You et al, 2014), while more research about proteome studies is needed to better understand the molecular changes associated with low BMD in OP and ON, especially in postmenopausal women who are more susceptible to experiencing fragility fractures.…”
Section: Introductionmentioning
confidence: 99%